PENGEMBANGAN MODEL INKUIRI SOSIAL DALAM PEMBELAJARAN ALQURAN-HADIS: PENELITIAN PENGEMBANGAN DI MADRASAH TSANAWIYAH (Development of Social Inquiry Model In Learning of The Quran-Hadith: Development Research In Madrasah Tsanawiyah) - Rahmiati Rahmiati; Muhamad Rezi; Muhammad Zubir (Jurnal Ilmiah Didaktika, 2021)
Learning the Quran and Hadith is one of the subjects given at Madrasah Tsanawiyah. Ideally, this learning effectively achieves the goals of National education, especially those related to understanding the main points of Islamic teachings and the proper way of practicing them in everyday life. Preliminary studies indicate that learning the Quran and Hadith is still not able to achieve the goals or ideals outlined by the curriculum. The Quran and Hadith material still dominantly emphasizes memorization/knowledge and is still far from solving problems (problem-solving skills). This study aims to develop learning the Quran and Hadith to instill the values of social care and become learning that challenges students' intellect and curiosity. The method used in this research is Research and Development, which steps in the form of a Preliminary Study, Development, and Product Testing. The development of the Social Inquiry model in learning the Quran and Hadith is significantly proven to be able to the teacher's social inquiry stating that in implementing learning, developing student creativity increases in learning. It can be interpreted that learning the Quran and Hadith based on social inquiry is practical to be implemented.